Karakteristik dan Kualitas Daging Sapi di Rumah Potong Hewan (RPH) Kota Ternate - Fenny Afrita; Yusnaini B. Talebe; Abdurrahman Hoda (Universitas Khairun, 2022)
The present study aimed at analyzing the weight of beef cattle meat at different ages, the carcass and percentage of the carcass of beef cattle using the Schoorl prediction formula and scale measurement, as well as examining the quality of beef cattle meat from the slaughterhouse. The samples were taken from 16 beef cattle. The quality of the meat was observed on the parts of leg, breast, and chuck of the cattle that were stored at the temperature of -20Â°C. The observation on the quality of the meat was carried out to find out the Total Plate Count (TPC), Water-holding Capacity (WHC), cooking shrinkage, and the pH of the meat. The results showed that samples from the 16 beef cattle consist of Ongole grade cattle and Balinese cattle within the age range of 3 - 6 years old. The weight of the beef cattle predicted with the Schoorl formula ranged from 222,84 to 298,50 kg, whilst the weight on the scale measurement basis indicated a range between 134,83 and 195,60 kg. The statistical analyses showed a significant difference (P0.05) between the carcass percentage calculated from the Schoorl prediction formula and from the scale measurement with a deviation of 12,340%. Yet, the TPC values showed an insignificant difference among the 16 beef cattle. Further, the quality of meat parts had an interaction with the length of storing in association with the cooking shrinkage of the beef cattle meat.Keywords: beef cattle weight, carcass, cooking shrinkage